MOTIVATION OF ENGAGEMENT OF STUDENT YOUTH OF UKRAINE IN VOLUNTEER ACTIVITIES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2024)
Background. The youth volunteer movement in Ukraine is a powerful and rapidly developing phenomenon. We can trace the surge in the development of this movement in the period from the full-scale invasion of Russia and the territory of Ukraine in February 2022, where ordinary volunteer assistance began to acquire signs of professionalism, a tried-and-tested mechanism and the selection of people to involve them in volunteer activities. Thus, from 2022 to 2023, new organizations are created, special centers are opened, relevant legislation is developed, and whole communities are organized to develop such a movement. A significant drawback in such an intensive surge is attracting suitable volunteers for professional activities.Methods. Theoretical and methodological analysis, questionnairesResults. Undoubted contribution in this direction can be called the efforts of every Ukrainian, who exert their maximum strength to support the Ukrainian army and the civilian population and protect children. However, when it comes to qualification in volunteer activities, it would be appropriate to consider it broadly to find possible options for involving young people in volunteer initiatives. In this context, it is essential to understand what needs to be done to work effectively with the volunteer community, particularly the youth, who potentially make up a more significant percentage of volunteers in today's conditions.Сonclusions. The article notes that Ukrainian youth see their future in Ukraine and are ready to participate in its creation today actively. Its support, creation of appropriate conditions, and development of programs/projects specifically for youth should become a vital issue of the state's social policy. Therefore, developing volunteer initiatives and supporting young people in this direction is an urgent issue today. Accordingly, the involvement of more young people in the volunteer movement will contribute to the development of social work because volunteering is one of its directions which helps overcome difficulties for clients of social work.
Keywords: volunteering; volunteer movement; youth; motivation; social work